AN ANALYSIS OF THE USE OF LANGUAGE VARIATION IN THE DIALOQUE OF DESIGNATED SURVIVOR FILM - Hastuti, Erni; Freely, Janice Debora; Oswari, Teddy (Universitas Gunadarma, 2024)
Language variation arises from social interactions and reflects a speaker's ability to adapt their communication style to different contexts and purposes. In Sociolinguistics, the choice of a language variety is influenced by the speaker's need for an appropriate communication situation. This research examines the use of language variation in the film Designated Survivor. The analysis was based on the five language variations proposed in Martin Joos’s theory. This study employs a descriptive-qualitative method. This analysis identified 129 language variation: 2 frozen styles, 40 formal styles, 48 consultative styles, 36 casual styles, and 3 intimate styles. The consultative style found as the dominant style in this research due to many existing meetings and negotiations in which both the speaker and the addressee convey their argument, opinion, and point of view about the topic being discussed.